1976
DOI: 10.1103/physrevlett.37.823
|View full text |Cite
|
Sign up to set email alerts
|

High-Spin Multiquasiparticle Yrast Traps inHf176

Abstract: We have identified several high-K four-and six-quasiparticle states between 2 0 5 and 5 MeV excitation in 176 Hf, which are well described by the collective model with axial symmetry,, Isomers with K n = 14", 19 + , and 22" form traps at or near the yrast line. The yrast structure changes from the ground band to a K v = 16 + band at J = 16 and again to a K n =22" state at 7 = 22, providing the first demonstration that intrinsic excitations of a heavy deformed nucleus can become yrast.An etch parameter almost u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(23 citation statements)
references
References 6 publications
0
22
0
1
Order By: Relevance
“…All transitions reported earlier were confirmed, but no new transitions below the 401 µs isomer were observed. While a rotational band built on this isomer had been observed in the earlier studies up to a 20 − state [7], this band was not reported to be fed by any isomeric state. Here, we present evidence that this band is being fed by an isomer.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…All transitions reported earlier were confirmed, but no new transitions below the 401 µs isomer were observed. While a rotational band built on this isomer had been observed in the earlier studies up to a 20 − state [7], this band was not reported to be fed by any isomeric state. Here, we present evidence that this band is being fed by an isomer.…”
Section: Resultsmentioning
confidence: 53%
“…Five isomeric states are known in 176 Hf with halflives ranging from 34 ns to 401 µs [5][6][7]. The present analysis reports on out-of-beam data and transitions above the K π = 14 − isomer (t 1/2 = 401µs) at 2866 keV excitation energy.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The well-deformed Hf nuclei (in particular 172 Hf) are known to possess a set of high K isomers [11][12][13]. This gives good support for axial symmetry in these nuclei and K, the projection of angular momentum onto the symmetry axis, can be considered an approximately good quantum number.…”
Section: Introductionmentioning
confidence: 99%